DOI: 10.29007/67nl
|View full text |Cite
|
Sign up to set email alerts
|

ICT for Sustainable Last-Mile Logistics: Data, People and Parcels

Abstract: In this paper we present a vision of how ICT can be leveraged to help combat the impact on pollution, congestion and carbon emissions contributed by the parcel delivery sector. This is timely given annual growth in parcel deliveries, especially same-day deliveries, and the need to inform initiatives to clean up our cities such as the sales ban on new petrol and diesel vehicles in the UK by 2040. Our insights are informed by research on parcel logistics in Central London, leveraging a data set of parcel manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Bates et al ( 38 ), found from GPS data that stem mileage represented 50.26% in a last-mile study in central London. Now, the distance run in the delivery area is also 50% of the total cycle.…”
Section: Case Study Of the Metropolitan Area Of Barcelonamentioning
confidence: 99%
“…Bates et al ( 38 ), found from GPS data that stem mileage represented 50.26% in a last-mile study in central London. Now, the distance run in the delivery area is also 50% of the total cycle.…”
Section: Case Study Of the Metropolitan Area Of Barcelonamentioning
confidence: 99%
“…Data from London has been used given that no data with this level of detail was available to the authors from NYC. It has been assumed that the handover time in NYC and London should be similar as the population density is similar (NYC: 10,429 km 2 [39]; Inner London 11,352 km 2 [40]), parking pressure and parking fines are a problem in both cities [41], and both cities had/have pedestrian couriers delivering parcels to central areas [42]. The time it takes to deliver parcels to the customer's home is calculated as follows:…”
Section: Delivery Tour Duration and Parking Timementioning
confidence: 99%
“…The culminating part of transportation in the logistical chain is also referred to a s the "last mile" phrase [3]. Last-mile delivery refers to the final phase in the process of delivery.…”
Section: Introductionmentioning
confidence: 99%